Perception of Family Support in Married and Working Female Students - Titi Soleha; Siti Rohmah Nurhayati (Universitas Pendidikan Ganesha, 2025)
Working and married college students face unique challenges in pursuing higher education and the world of work. Support from family members can have a significant impact on the ability of married and working students to cope with stress, maintain balance, and perform their roles as students and workers well. This study was conducted to determine the perception of family social support in married and working female students and to determine the form of family support received by female students. The method used in this study is a qualitative case study method. The process of selecting participants using purposive sampling technique so that the number of participants is 4 participants. Data collection techniques using semi-structured interviews. The results of this study were that all participants expressed their perceptions of the family support they received. Family support that includes emotional, informative, instrumental, and appreciation support has a positive impact on their daily lives. All participants were satisfied with the support provided by their families, bringing benefits such as feeling helped, comfortable, calm in facing problems, enthusiastic, and relaxed in living life.